Effects of Gibberellic Acid (GA3) and Salicylic Acid (SA) postharvest treatments on the quality of fresh Barhi dates at different ripening levels in the Khalal maturity stage during controlled atmosphere storage - Atia, Ahmed; Abdelkarim, Diaeldin; Younis, Mahmoud; Alhamdan, Abdullah (International Journal of Agricultural and Biological Engineering, 2018)
Barhi dates at Khalal maturity stage are well-known with their pleasant taste, crispy texture, and bright yellow color. It is necessary to extend the duration of Barhi Khalal stage which is too short for effective marketing. This study aimed to inspect the effects of Gibberellic Acid (GA3) and Salicylic Acid (SA) postharvest treatments on retaining the high quality of Khalal Barhi fruits during controlled atmosphere storage. Fresh samples of Barhi fruits at Khalal stage harvested at three different ripening levels were dipped after harvesting in GA3 (150 ppm) or SA (2.0 mmol/L) and subsequently stored in controlled atmosphere (0°С, 5% O2, 5% CO2, 80%±5% RH). The results revealed that the GA3 and SA treatments reduced the percentage of weight loss and decay in the fruits, while the total soluble solids increased. Moreover, GA3 and SA treatments were significantly efficient in limiting the changes in fruit color and texture of Barhi dates compared to the control. Sensorial results support the experimental data and disclosed that the GA3 (150 ppm) treatment in the controlled atmosphere (CA) storage was better in conserving the quality of Barhi at the Khalal maturity stage and delaying ripening process.Keywords: Barhi dates, Khalal maturity stage, Gibberellic Acid (GA3), Salicylic Acid (SA), postharvest treatments, controlled atmosphere (CA) storageDOI: 10.25165/j.ijabe.20181103.3760Citation: Atia A, Abdulkarim D, Younis M, Alhamdan A. Effects of gibberellic acid (GA3) and salicylic acid (SA) postharvest treatments on the quality of fresh Barhi dates at different ripening levels in the Khalal maturity stage during controlled atmosphere storage. Int J Agric & Biol Eng, 2018; 11(3): 211–219.